Protective effects of camel milk and vitamin E against monosodium glutamate induced biochemical and testicular dysfunctions - El-Sawy, Hanan Basiouni Ismail; Soliman, Mohamed Mohamed; El-Shazly, Samir Ahmed; Abdel-Maksoud Ali, Hussein (Progress in Nutrition, 2018)
Objective: The current study was outlined to examine the protective effects of camel milk (CM) against the deleterious effects induced by monosodium glutamate (MSG). Methods: MSG was administered either alone or in combination with camel milk or vitamin E for 4 weeks. Serum and testicular tissues were examined using semiquantitative RT-PCR analysis. Results: CM normalized the decrease in serum levels of testosterone, luteinizing hormone (LH), sperm profiles and testicular antioxidant activities that were decreased by MSG. At the molecular levels, MSG down-regulated the mRNA expression of steroidogenesis related genes and receptors of androgen, LH and follicle stimulating hormone. MSG induced testicular apoptosis. All altered genes were normalized and upregulated in presence of CM when compared to the effect of Vit. E. Conclusions: The usage of camel milk as a therapy against MSG used in food industry is very indicative and protective.